SUPERVISI KEPALA SEKOLAH MEMODERASI PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA GURU SUB RAYON 01 SMK NEGERI KOTA SEMARANG - Endang Sri Wartini, 12.52.02.0223; Basiya, R. (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to examine and analyze the relationship of teacher competence, discipline and supervision of principals on teacher performance. Research questions posed in this study are (1) how competence affect the performance of teachers, (2) how disiplini affect the performance of teachers (3) How supervising the principal influence on the performance of teachers (4) Is the principals supervision moderating influence on the performance of competence teacher (5) Is the principal moderate supervision disciplinary influence on teacher performance. The study population was a teacher at SMK SMK sub rayon 01 Semarang as much as 234. The samples using purposive sampling, in order to get a sample of 113 respondents. The method of data collection is by using a questionnaire. Technical analysis of data using multiple regression. The results showed that the effect on the performance of teacher competence, discipline and significant positive effect on teacher performance. supervision of the principal influence on teacher performance. supervision of the principal does not memodersi relation to the performance of teacher competence.Keywords: Competence of Teachers, Discipline, Teacher Performance and Supervision of The Principal